ANALYSIS OF THE CHEMICAL AND ORGANOLEPTIC CONTENT OF BELSASIKUNTAS AS A HEALTHY DRINK INNOVATION - Wilujeng, Sukian; Widya, Surya Ari; Bafiqi, Medita Johana Pakula; Isrianto, Pramita Laksitarahmi (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Belsasikuntas is a functional beverage made from a mixture of Wuluh star fruit, bay leaves, betel leaves, turmeric, and beluntas leaves. This study aims to analyze its polyphenol and vitamin C content using the Folin-Ciocalteu method for polyphenols and the iodometry method for vitamin C. Additionally, an organoleptic evaluation was conducted to assess color, aroma, and taste. Polyphenol and vitamin C content were tested both with and without dilution. For the diluted samples, a Completely Randomized Design method was applied with four concentration levels and five repetitions. The results for the undiluted samples showed that the highest polyphenol content (81.43 mg/100 mL) was observed at 5 mL, while the lowest (80.88 mg/100 mL) was recorded at 15 mL. The highest vitamin C content (48.01 mg/100 mL) was found at 15 mL, whereas the lowest (47.89 mg/100 mL) was at 5 mL. In diluted samples, the highest polyphenol content (81.36 mg/100 mL) was observed at 20 mL, while the lowest (27.54 mg/100 mL) was at 5 mL. The highest vitamin C content (47.93 mg/100 mL) was recorded at 20 mL, whereas the lowest (11.10 mg/100 mL) was found at 5 mL. The results indicate that polyphenol and vitamin C content decrease as more water is added. The organoleptic evaluation yielded a total public acceptance score of 100%, with 62% for color, 11% for taste, and 27% for fragrance. These findings suggest that Belsasikuntas has potential as a functional health drink with favorable consumer acceptability. Keywords: Belsasikuntas, Health Drink, Polyphenol, Vitamin C